The Art of Peace and Existential Therapy (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
We turn to some aspects of Zen Buddhist philosophy and use the examples of Aikido martial arts philosophy to explore what might be in common between psychotherapy and martial arts. We focus on existential therapy, which we see has much in common with the philosophy and spiritual practices of the Far East.
Keywords: Existential therapy; Aikido; Zen; love; death; dojo